Technology Utilization to Simplify Administrative Management and Communication in Residential Estate - Susana Limanto; Liliana Liliana; Steven Ming (Jurnal Komputer Terapan, 2021)
The increasing crime rate during Covid-19 pandemic has impact in the administration of entering and exiting residential estate on the one gate system to be complicated so it takes time and results in queues. On the other hand, under government recommendations to reduce mobility outside the home has disrupted the residential administration. Various housing applications that have been developed are still conducting administration in and out at residential gate conventionally and limiting access rights to applications only by residential members. Such an application has not overcome the problem of the length of the licensing administration process at the residential gate. In this paper, an android application with QR code technology is offered to assist residential administration while simplifying the administration of permits in and out of residential gate. The research was conducted using Waterfall method while to generate a QR code was used QRCodeWriter. Based on the interview, all parties involved stated that the application helped housing administration continued to run well despite restrictions on activities outside the home and simplified administration at the residential gate. But, at the user's point of view as resident, the application was considered inconvenient because they should to learn something new.